2018
DOI: 10.1139/cjm-2017-0544
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacillus-like bacterial community in the rhizospheric and non-rhizospheric soil of halophytes (Salsola stocksii and Atriplex amnicola), and characterization of osmoregulatory genes in halophilic Bacilli

Abstract: Salinity is one of the major abiotic stresses; a total of 3% of the world's land mass is affected by salinity. Approximately 6.3 million hectares of land in Pakistan is affected by salinity to varying degrees, and most of the areas are arid to semiarid with low annual precipitation. The aim of the present study is to identify and characterize Bacillus and Bacillus-derived bacterial genera from the rhizospheric and non-rhizospheric soil samples from the Khewra Salt Mine, Pakistan, by using culture-independent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
(25 reference statements)
5
20
0
Order By: Relevance
“…This observation is in agreement with an earlier study that found bacteria from the genus Bacillus being the most dominant genus isolated from Ixodes ticks in the United States (Martin & Schmidtmann, 1998). The predominance of these bacterial genera (Bacillus and Bacillus-derived genera) to environmental niches suggests that the isolated bacteria presumably originated from the environment too (Mukhtar et al, 2018). This finding should not be downplayed regardless, as environment-associated Bacillus sp.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is in agreement with an earlier study that found bacteria from the genus Bacillus being the most dominant genus isolated from Ixodes ticks in the United States (Martin & Schmidtmann, 1998). The predominance of these bacterial genera (Bacillus and Bacillus-derived genera) to environmental niches suggests that the isolated bacteria presumably originated from the environment too (Mukhtar et al, 2018). This finding should not be downplayed regardless, as environment-associated Bacillus sp.…”
Section: Discussionsupporting
confidence: 93%
“…6). Protease-producing alkaliphilic and halophilic bacteria such as Halobacillus karajensis and Halomonas meridiana have been previously isolated marine environments and food sources such as fish sauce [43,50]. Like protease, maximum amylase activity of Bacillus strains (AT2RP4, NRS4HaP9, and LK3HaP7) was also observed in the presence of 1.5 M NaCl, pH 7-8, and 37°C ( Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Members of the genus Staphylococcus (S. equorum, S. haemolyticus, and S. saprophyticus) were identified from the rhizosphere of Salsola and Atriplex and lake-bank soils. They are moderately halophilic strains and play an important role in plant growth and biodegradation of hemicelluloses and lipases [43,44]. Bacterial isolates related to Kocuria and Streptomyces were identified from the rhizosphere of halophytes as well as from the non-rhizospheric soils.…”
Section: Discussionmentioning
confidence: 99%
“…Many root endophytes can be used as biocontrol agents due to their production of different antibiotic and antifungal compounds [39]. Halotolerant and halophilic Bacillus spp, produce hydrolytic enzymes and have been reported as growth inhibitors for fungal pathogens and they provide protection for different plant diseases [26,40]. These microorganisms also produce a variety of hydrolytic enzymes and play an important role in suppressing the fungal pathogens such as Alternaria sp.…”
Section: Halophyte Rhizosphere and Root Endosphere Microbiomementioning
confidence: 99%